Development of methylated cobalt–alkyne complexes with selective cytotoxicity against COX‐positive cancer cell lines. Issue 2 (10th December 2021) - Baecker, Daniel; Sagasser, Jessica; Karaman, Serhat; Hörmann, Anton Amadeus; Gust, Ronald
Abstract: Derivatives of the cytotoxic cyclooxygenase (COX) inhibitor [(prop‐2‐ynyl)−2‐acetoxybenzoate]dicobalthexacarbonyl (Co‐ASS) with a methyl group in the 3, 4, 5, or 6 position of the acetylsalicylic acid (ASS) scaffold were synthesized with the aim to achieve enhanced selectivity for COX‐2. From this modification, a higher specificity for COX‐2‐expressing tumors is expected, preventing COX‐1‐mediated side effects. The cobalt–alkyne complexes were tested for their COX‐inhibitory and antiproliferative properties as well as their cellular uptake. Methylation reduced the effects at the isolated COX‐1, whereas those at the isolated COX‐2 remained nearly constant compared to Co‐ASS. In cellular systems, the new compounds showed superior cytotoxicity toward the COX‐positive HT‐29 colon carcinoma cells than cisplatin. The reduced growth‐inhibitory potency in T‐24 cells, which express distinctly fewer COX enzymes (COX‐1/COX‐2 = 50/1) than HT‐29 cells (COX‐1/COX‐2 = 50/50), and the only marginal activity in COX‐negative MCF‐7 breast cancer cells point to an interference in the arachidonic acid cascade through COX‐2 inhibition as part of the mode of action, especially as the cellular uptake was even higher in MCF‐7 cells than in T‐24 cells. These findings clearly demonstrate that the methylated cobalt–alkyne complexes possess promising potential for further development as reasonable alternatives to the limited platinum‐based antitumor agents. Abstract : The cyclooxygenase (COX) inhibitor [(prop‐2‐ynyl)−2‐acetoxybenzoate]dicobalthexacarbonyl (Co‐ASS) exerts its anticancer activity by inhibition of COX‐1/2. However, inhibition of COX‐1 is unwanted due to the severe side effects. Optimization of Co‐ASS by methylation of the aromatic ring indeed yielded antitumor‐active compounds showing less inhibition of COX‐1, thus obtaining the desired selectivity toward COX‐2.